2018
DOI: 10.1021/acs.chemmater.8b03579
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic-Directed Hydrogel Fabrics Based on Interfibrillar Self-Healing Effects

Abstract: Multistructural and versatile fibers have attracted enormous interests in various potential applications ranging from tissue engineering and cells to sensors. However, the controllable fabrication and nonwoven assembly of fibers remain a challenge. Here, we developed a novel strategy to in situ fabricate supramolecular hydrogel fibers via microfluidic spinning technology where self-healing fibers can be nonwoven assembled into fabrics through noncovalent interactions (host− guest interactions). We utilized β-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 51 publications
(72 reference statements)
1
44
0
Order By: Relevance
“…The final hydrogel microfiber net is well aligned, uniform and elastic, and can sustain a certain weight of load like a fishing net (Figure 1b). In principle, any woven 2D or 3D organized patterns with tunable fiber densities can be obtained with this method 19,27. As an example, three fiber nets with different fiber densities were obtained by changing the parallel movement speed of rotating collector (Figure S1, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The final hydrogel microfiber net is well aligned, uniform and elastic, and can sustain a certain weight of load like a fishing net (Figure 1b). In principle, any woven 2D or 3D organized patterns with tunable fiber densities can be obtained with this method 19,27. As an example, three fiber nets with different fiber densities were obtained by changing the parallel movement speed of rotating collector (Figure S1, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…To circumvent this issue, recently Ma et al reported a core–shell stretchable and conductive sodium polyacrylate hydrogel microfiber with a thin elastomer coating layer to prevent dehydration while maintaining good fiber elasticity 14. Nonetheless, the inert elastomer coating evitably leads hydrogel microfiber to be insensitive to environmental changes, which are unfavorable for sensing applications. Spinnability versus fiber strength: compared to electrospinning15,16 and extrusion spinning,9,10,17,18 microfluidic or draw‐spinning inspired from spider spinning procedure11–14,19,20 seems to be more suitable for fabricating long and uniform hydrogel microfibers. However, unless using the strategy of full dehydration, it is still challenging to compromise the spinnability and mechanical strength of hydrogel microfibers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Common molecules used to form host-guest interaction include crown ethers (Xue et al, 2015), calixarenes (Yan et al, 2012), cucurbiturils (Appel et al, 2012), pillararenes (Ogoshi et al, 2016), and cyclodextrins (CDs) (Deng Z. et al, 2018;Li Q. et al, 2018;Wang et al, 2019e;Wu et al, 2008). The authors (Li Q. et al, 2018) used β-cyclodextrin and N-vinylimidazole to achieve hydrogel fibers. The self-healing experiment showed that the cut hydrogel fibers could adhere together within 24 h, and the healed fiber could withstand a reversible stretch.…”
Section: Host-guest Interactionmentioning
confidence: 99%
“…Dynamic covalent bonds include imine bond ( Qu et al, 2017 ; Yan et al, 2017 ; Chen H. et al, 2018 ; Chen et al, 2019e ; Khan et al, 2018 ; Wei and Gerecht, 2018 ; Zhang et al, 2018 ; Guo B. et al, 2019 ; Jiang F. et al, 2019 ; Li Q. et al, 2019 ; Qian et al, 2019 ; Wang et al, 2019b ; Wang W. et al, 2019 ; Zhou et al, 2019 ), Diels–Alder (DA) reaction ( Oehlenschlaeger et al, 2014 ), boronate-diol complexation ( Hong et al, 2018 ; Pan et al, 2018 ; Smithmyer et al, 2018 ; Zhi et al, 2018 ; Han et al, 2019 ), acylhydrazone bond ( Yang et al, 2017 ; Shen et al, 2019 ; Sun C. et al, 2019 ), dynamic disulfide bond ( Song L. et al, 2019 ), and dynamic metal oordination ( Shao et al, 2018 ; Chen et al, 2019a ; Qin et al, 2019 ). Physical non-covalent interactions include hydrogen bonding ( Fan et al, 2018 ; Uzumcu et al, 2018 ; Cao et al, 2019 ; Chen et al, 2019c ; Hu et al, 2019 ; Huang et al, 2019 ; Kuddushi et al, 2019 ; Li R. et al, 2019 ; Liao et al, 2019 ; Su et al, 2019 ; Wang L. et al, 2019 ), hydrophobic interaction ( Liu P. et al, 2019 ), host-guest interaction ( Deng Z. et al, 2018 ; Li Q. et al, 2018 ; Liu L. et al, 2019 ; Wang W. et al, 2019 ), and ionic interaction ( Ma et al, 2018 ; Wang Y. et al, 2018 ; Becher et al, 2019 ). Some intrinsic type self-healing hydrogels even have several kinds of networks, containing either one type or several types of mechanisms.…”
Section: Introductionmentioning
confidence: 99%